2021
DOI: 10.1186/s13073-021-00898-8
|View full text |Cite
|
Sign up to set email alerts
|

Tumor fraction-guided cell-free DNA profiling in metastatic solid tumor patients

Abstract: Background Cell-free DNA (cfDNA) profiling is increasingly used to guide cancer care, yet mutations are not always identified. The ability to detect somatic mutations in plasma depends on both assay sensitivity and the fraction of circulating DNA in plasma that is tumor-derived (i.e., cfDNA tumor fraction). We hypothesized that cfDNA tumor fraction could inform the interpretation of negative cfDNA results and guide the choice of subsequent assays of greater genomic breadth or depth. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Unfortunately, availability of tumor DNA is often a limiting factor for NGS-based studies. Liquid biopsies could be a reliable source of tumor DNA for such purposes, as significant numbers of clinically actionable variants have been present in cell-free DNA samples when tumor samples were either unavailable or had not yielded any results ( 192 ). Similar conclusions can be drawn from studies utilizing mutation-specific PCR ( 193 ) and methylation analysis ( 194 , 195 ) of cell-free DNA from patients with metastatic disease.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Unfortunately, availability of tumor DNA is often a limiting factor for NGS-based studies. Liquid biopsies could be a reliable source of tumor DNA for such purposes, as significant numbers of clinically actionable variants have been present in cell-free DNA samples when tumor samples were either unavailable or had not yielded any results ( 192 ). Similar conclusions can be drawn from studies utilizing mutation-specific PCR ( 193 ) and methylation analysis ( 194 , 195 ) of cell-free DNA from patients with metastatic disease.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…The study investigating mutations in cfDNA had 10 recruited patients with TGCT and 10 healthy controls. 32 Of the 10, NGS analysis of cfDNA and tumor genomic DNA has managed to identify mutations in six patients, while the remaining four have not had any mutations detected. Of the six, four patients had mutations present in the tumor, which were also detected in the cfDNA of three patients, and undetected in one.…”
Section: Resultsmentioning
confidence: 99%
“… 59 , 60 This would make most commercial cfDNA assays, which are highly focused, not well suited for TGCT, and more broader sequencing assays should be employed which remain cost-prohibitive for near-term clinical implementation. 32 , 49 This is only additionally complicated by ultra-deep sequencing picking up inconsequential mutations in other high turnover components (such as bone marrow) when needing to interpret rare alleles. 19 As research has shown, 32 while 6 of the 10 TGCTs have been detected by NGS, only 3 of them have had the same mutations identified in cfDNA and DNA from the solid tumor, 2 have had mutations detected only in cfDNA (which could be the before-mentioned inconsequential mutations), and 1 had tumor mutations not detected in cfDNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, we must acknowledge that the true positive fraction of cases could be underestimated because of the limited sensitivity of the tests that we used. In this respect, the estimation of tumor fraction in plasma samples might in the future allow for a better definition of this phenomenon [ 44 , 45 , 46 ]. Studies on larger patients’ cohorts will allow us to better define the prognostic value of acquired, likely sub-clonal RAS and BRAF variants, which could be different as compared with de novo clonal mutations of these genes.…”
Section: Discussionmentioning
confidence: 99%